Geochemical significance of arsenic and manganese toxicity in groundwaters from Murshidabad district, West Bengal, India - Sasidharan, Sankar Manalilkada (Kansas State University, 2013)
Mass poisoning of arsenic (As) has affected roughly 60 million people in the Bengal Basin (Bangladesh and West Bengal, India) and 43 million people alone in West Bengal. Elevated levels of Manganese (Mn) is another alarming issue in the groundwaters of this region (MCLs: As<10µg/L and Mn< 0.4mg/L). Four locations in Murshidabad district (south-central part of Bengal Basin) were chosen for this current study. Among the 4 locations, two of them showed high concentration of As (>50 - 4622µg/L; 2009 survey) and they are Beldanga: 23° 56'N& 88°15'E and Hariharpara: 24°3.68'N & 88° 21.63'E. On the other hand: Nabagram (24°12.08'N & 88°13.29'E) and Kandi (23°58.6'N & 88°6.68'E) demonstrated less dissolved As (<10µg/L) in groundwaters. Study areas were located to the west (Nabagram, Kandi) and east (Beldanga, Hariharpara) of the river Bhagirathi, a tributary of the river Ganges, flowing N-S through the district of Murshidabad. Eastern side of the river is occupied by grey colored Holocene sediments and western side has more oxidized orangish-brown Pleistocene sediments. Comparative study of major water quality parameters between these sites revealed high As (10-1263µg/L) and low Mn (0.1-1.3mg/L) in the areas like Beldanga, Hariharpara while low As (0-15µg/L) and higher Mn (0.2-4.2mg/L) in Nabagram and Kandi. The pH range for high and low As areas were 4.5-7.8 and 5.1-8.2 respectively. Phosphates showed values <0.04-2.21mg/L in high As areas and <0.08-2.52mg/L in low areas whereas Cl- values were higher within low As areas (29-200mg/L) and lower within high As areas (3.9-78.4mg/L). Fe(t) and Fe2+ values at high and low As areas were 0-13.5mg/L, 0.01-0.11mg/L and 0-1.4mg/L, 0.04-0.06mg/L respectively. δ18O and δD results revealed that monsoonal precipitation is the major recharge source in this area with some input from the surficial waterbodies as ponds in shallower depths within high As areas. The total As extracted from core sediments in these areas do not show much difference: total As in high and low As areas ranges from 6.4-18 mg/kg. Sequential extraction results revealed that majority of the sediment bound As is present in residual phases (>40%). DOC in groundwaters in high and low As areas were 1.5-3.2 and 0.5-1.3mg/L respectively and they had positive correlation with As within the depth profiles. Dissolved organic matter (DOM) characterization studies indicated that microbial proteins (Tyrosine and Tryptophan) are the major components in the groundwaters in the low As region, whereas high As area groundwaters tend to have higher content of humic DOM (A and C). Cl/Br molar ratio of high As wells were low compared to the low As wells. Current study revealed the importance of organic matters (and not the mineralogy of the sediments) both in sediments and groundwaters in controlling the release of As from sediment, at least in the shallow parts of Bengal delta aquifer and microbial mediated reductive dissolution of FeOOH in the presence of organic matter is the major mechanisms by which sediment bound As (<50m depth) is released into the groundwater. The darker organic matter rich sediments (OM both sediment bound and anthropogenically derived) existing at the depth range 20m-50m with reducing environment persisting in both high and low As areas are possible reasons for elevated levels of As in this region.
Keywords: Arsenic; Manganese; Bengal basin; Murshidabad; Dissolved organic matter; Cl/Br ratio; Geochemistry (0996); Geology (0372); Hydrologic Sciences (0388)